Mulheres artistas: notas sobre estratégias curatoriais, questões de gênero e raça e de empoderamento - Daphne Emanuelle Silva Cunha (2019)
In the last decade there have been a considerable number of art exhibitions that purported to exhibit works produced by women. Collectively or individually, structured from a thematic axis or considering only the gender issue, such expositions collaborate in a systematic way in the expansion of the visibility of women artists and in the change of paradoxes that cross the patriarchal society in the political and social sphere, and more circumstantially in the institutions where art develops. Although the critical propositions that question the relationship between art and gender have been consolidating since the early manifestations of the feminist movement, and more effectively with the revolutionary movements of the 1960s and 1970s - the black movement, the sexual revolution, the movement the counterculture and the feminist movement - it is still necessary to think of strategies of legitimacy and equivalence to expose works of art produced by women, without ignoring the complexity raised by a possible segregation. This dissertation presents two exhibitions that, due to their structural and theoretical dimensions, denote a considerable scope at the national level - since they were the two largest exhibitions of this category to be exhibited in Brazil - and overall, since they were conceived in important nucleo of Western artistic diffusion: "Elles: women artists in the collection of the Center Pompidou" and "Radicals women: Latin American art, 1960-1985". Through these expositions the research is structured based on a series of questions. What strategies are in place? Is it possible to think of a curatorship that demonstrates the artistic production of women without conditioning them to gender segmentation? And, finally, what is the role of these curatorial proposals in public awareness?